Social Protection and Foundational Cognitive Skills during Adolescence: Evidence from a Large Public Works Programme - Richard Freund; Marta Favara; Catherine Porter; Jere R. Behrman (Institute of Labor Economics (IZA), 2022)
Many low- and middle-income countries have introduced Public Works Programmes (PWPs) to fight poverty. PWPs provide temporary cash-for-work opportunities to boost poor households' incomes and to provide better infrastructure to local communities. While PWPs do not target children directly, the increased demand for adult labour may affect children's development through increasing households' incomes and changing household members' time uses. This paper expands on a multidimensional literature showing the relationship between early life circumstances and learning outcomes and provides the first evidence that children from families who benefit from PWPs show increased foundational cognitive skills (FCS). We focus on four child FCS: inhibitory control, working memory, long-term memory, and implicit learning. Our results, based on unique tablet-based data collected as part of a 20- year longitudinal survey, show positive associations of family participation in the Productive Safety Net Programme (PSNP) in Ethiopia during childhood on long-term memory and implicit learning, with weaker evidence for working memory. These associations appear to be strongest for children whose households were still PSNP participants in the year of data collection. We find suggestive evidence that, the association with implicit learning may be operating through children's time reallocation away from unpaid labour responsibilities, while the association with long-term memory may be due to the programme's success in remediating nutritional deficits caused by early life rainfall shocks. Our results suggest that policy interventions such as PWPs may be able to mitigate the effects of early poverty on cognitive skills formation and thereby improve children's potential future outcomes.
Keywords: J24; I2; I1; 330; foundational cognitive skills; Ethiopia; public works programmes; PSNP; skills development